Italian and Spanish commercial tomato sauces for pasta dressing: study of sensory and head‐space profiles by Flash Profiling and solid‐phase microextraction‐gas chomatography‐mass spectrometry. (27th January 2017) - Bendini, Alessandra; Vallverdú‐Queralt, Anna; Valli, Enrico; Palagano, Rosa; Lamuela‐Raventos, Rosa Maria; Toschi, Tullia Gallina
Abstract: BACKGROUND: The sensory and head‐space profiles of Italian and Spanish commercial tomato sauces were investigated. The Flash Profiling method was used to evaluate sensory characteristics. Samples within each set were ranked according to selected descriptors. One hundred volatile compounds were identified by solid‐phase microextraction‐gas chomatography‐mass spectrometry. RESULTS: For Italian samples, the sensory notes of basil/aromatic herbs, acid and cooked tomato were among those perceived most by the assessors, whereas, in Spanish samples, the sensory attributes of garlic/onion and onion/sweet pepper and, in Italian samples, cooked tomato were among those found most frequently. Data were elaborated using multivariate statistical approaches and interesting correlations were observed among the different sensory attributes and related volatile compounds. CONCLUSION: Spanish samples were characterized by the highest content of volatiles linked to the thermal treatment of tomatoes and to raw and sautéed garlic and onion, whereas the Italian samples were characterized by terpenic compounds typical of basil and volatile molecules derived from fresh tomato. These results confirm the influence of both formulation and production processes on the aromatic profile (sensory attributes and volatile compounds) of tomato products, which is probably related to the different eating habits and culinary traditions in Italy and Spain. © 2016 Society of Chemical Industry